An applied examination of the computerized adaptive rating scale for assessing performance. (June 2017) - Darr, Wendy; Borman, Walter C.; St‐Pierre, Line; Kubisiak, Christean; Grossman, Matthew
Abstract: In the present research, we developed and conducted a field test of the computerized adaptive rating scale (CARS) for assessing military officer performance. Participants completed the CARS and a behaviorally anchored rating scale (BARS) which were both designed to assess five leadership competencies (action orientation/initiative, communication, developing self and others, behavioral flexibility, and teamwork). We obtained data from 116 supervisors and 207 peers who provided ratings on 126 officer ratees. Although interrater reliability estimates were lower for CARS ratings on some competencies, there was a 20–25% improvement in standard error of measurement, the measurement precision in CARS ratings compared to the BARS. Results support findings from a previous lab study.